Job insecurity Akibat Pandemi Covid-19: Studi Kasus Anggota Komunitas Lava Tour Kelurahan Umbulharjo - Syahrani, Lutfi Syahwa (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2024)
The eruption of the Covid-19 pandemic significantly impacted tourism activities in the Lava Tour sector within the Umbulharjo Village of Cangkringan, sparking concerns among locals regarding the looming threat of job insecurity, particularly among jeep drivers. In light of this, fostering strong personal resilience becomes crucial in tackling the issue of job insecurity. This research aims to shed light on how members of the 13 Lava Tour jeep communities in Umbulharjo Village managed to navigate, adapt to, and eventually recover from job insecurity. The Conservation of Resources Theory (COR), outlined by Hobfoll (2018), serves as the framework to analyze this resilience. Results indicate that community members indeed faced job insecurity, experiencing temporary unemployment and a profound sense of helplessness due to lacking support networks within the community, the Asosiasi Jip Wisata Lereng Merapi Sisi Timur, and the government. However, the resources played a crucial role in enabling them to confront this challenge. Consequently, members of the Lava Tour tourism community in Umbulharjo Village demonstrated enhanced individual resilience after the pandemic, notably through implementing financial management practices such as savings programs and introducing innovative shifts in their marketing strategies.